Validation of the Geriatric Oral Health Assessment Index (GOHAI) in the Malay language - Wan-Nasir W. Othman; Khairiyah A Muttalib; Rugayah Bakri; Jennifer G Doss; Nasruddin Jaafar; Natifah C Salleh; Sharon Chen (Wiley Online Library, 2024)
Non-Indexed Publication